Preformulation Parameters Characterization towards Design, Development and Formulation of Etodolac Loaded Nanoparticles - Saminathan C (Journal of Global Pharma Technology, 2021)
The purpose of the present study was to systematically investigate some of the important physicochemical properties of Etodolac loaded nanoparticles. Etodolac is a non-steroidal anti-inflammatory drug, is used to manage rheumatoid arthritis associated symptoms. Almost all drugs are marketed as tablets, capsules or both. Prior to the development of these major dosage forms, it is essential that pertain fundamental physical and chemical properties of the drug molecule and other divided properties of the drug powder are determined. This information decides many of the subsequent events and approaches in formation development. A modified release nanoparticle of Etodolac was prepared by solvent evaporation method using EUTRAGIT RS 100 as coating material. Hence along with selection of excipients, the preformulation study of drug Etodolac is completed for successful formulation of modified release nanoparticles. Preformulation studies included solubility, pKa, dissolution, melting point, assay development, stability in Solution, stability in solid state; microscopy, bulk density, flow properties, excipients compatibility, entrapment efficiency and release profile of nanoparticles were investigated. The experimental values and results of this study will be presented. Keywords: Nanoparticles, Entrapment efficiency, Etodolac, EUTRAGIT RS 100, Preformulation.